PENGARUH PRICE DAN PRODUCT QUALITY TERHADAP CONSUMER PURCHASE DECISION PADA PT SEMEN HOLCIM BATAM - Jurnal Ilmiah Manajemen UPB (Universitas Putera Batam, 2017)
Consumers are one of the key factors determining the success or failure of companies in marketing their products. Companies must know and understand consumer behavior on the target, so that each company should be able to understand the viability of the company and work hard to make policy in creating new strategies for their products face stiff competition in which competitors can make the customer's purchasing decision. The purpose of this study was to investigate and analyze: Influence of Price and Quality Products Buying Decision Against Holcim At PT Semen Batam. Based on the results of research and discussion that has been described, it can be concluded that the variable price and quality of products influence purchasing decisions in PT Semen Batam Holcim. The coefficient of determination (R) indicates that the variable quality of the product is able to explain 93.9% of purchase decisions, while the rest is explained by other variables not included in this study.